2016
DOI: 10.1038/srep39429
|View full text |Cite
|
Sign up to set email alerts
|

A polymorphism of HMGA1 protects against proliferative diabetic retinopathy by impairing HMGA1-induced VEGFA expression

Abstract: Diabetic retinopathy (DR) is a major complication of diabetes mellitus, and is the leading cause of blindness in working-age people. Usually, DR progresses from the asymptomatic non-proliferative DR that does not significantly alter vision, to proliferative DR (PDR), which can result in aberrant retinal neovessel formation and blindness. The High-Mobility-Group A1 (HMGA1) protein is a transcriptional master regulator of numerous genes, including metabolic and inflammatory genes, which, by modulating the expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Participants were recruited only from endocrinological outpatient clinics within the Catanzaro area, assuring simplified communication channels between practitioners and medical researchers, and small variability regarding data collection. Furthermore, we took advantage of the comparatively genetic homogeneity of the Calabrian population [43][44][45], which may allow for a small inter-individual variability in pharmacological responses [46,47]. Nonetheless, our results can only be applied to patients who show a positive response to Liraglutide and no safety concerns, which would otherwise prevent a 5-year prolonged therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were recruited only from endocrinological outpatient clinics within the Catanzaro area, assuring simplified communication channels between practitioners and medical researchers, and small variability regarding data collection. Furthermore, we took advantage of the comparatively genetic homogeneity of the Calabrian population [43][44][45], which may allow for a small inter-individual variability in pharmacological responses [46,47]. Nonetheless, our results can only be applied to patients who show a positive response to Liraglutide and no safety concerns, which would otherwise prevent a 5-year prolonged therapy.…”
Section: Discussionmentioning
confidence: 99%
“…We noted that very few population studies were performed to explore the biomarkers that are associated with DR severity. 17 Most of the studies recruited small numbers of NPDR and PDR patients (n ¼ 19-473) 5,[18][19][20] or exclusively PDR subjects (n ¼ 9-42). 4,[21][22][23][24] Although ANGPTL4 has been found increased in PDR patients, the number of patients ranged from 28 to 53.…”
Section: Multivariable-adjusted Analysesmentioning
confidence: 99%
“…Therefore, the risk of intravitreal infection is much higher and some patients also respond poorly to anti-VEGF treatments [42] .Thus, identification of novel targets that play important roles in retinal neovascularization is urgently needed for those not responsible for anti-VEGF therapy [43] . Studies also demonstrated that celecoxib could inhibit the expression of VEGF and neovascularization growth in retinal pigment epithelial cells and the effect was mediated through a PI3K/AKT-dependent manner [44] and abrogating of VEGF significantly reduced the risk of developing to PDR in type 2 diabetes patients [45] .…”
Section: Discussionmentioning
confidence: 97%